Aerodynamic analysis of civil aeroengine exhaust systems using computational fluid dynamics - Otter, John J.; Goulos, Ioannis; MacManus, David G.; Slaby, Michal (AIAA, 2018)
As the specific thrust of civil aeroengines reduces, the aerodynamic performance of the exhaust system will become of paramount importance in the drive to reduce engine fuel burn. This paper presents an aerodynamic analysis of civil aeroengine exhaust systems through the use of Reynolds-averaged Navier–Stokes computational fluid dynamics. Two different numerical approaches are implemented, and the numerical predictions are compared to measured data from an experimental high-bypass-ratio separate-jet exhaust system. Over a fan nozzle pressure ratio range from 1.4 to 2.8, a comparison is drawn between values of the thrust coefficient calculated numerically and those obtained from experimental measurements. In addition, the effects of the freestream Mach number and extraction ratio on the aerodynamic behavior of the exhaust system are quantified and correlated to fundamental aerodynamic parameters.
Keywords: Gas turbine; Aerodynamics; Computational fluid dynamics; Exhaust; Nozzles; Turbofan